Foreign Capital and SEO Valuation – Evidence from Sweden - Ringström,Matys; Samuelsson,William (2025)
This thesis examines how investor nationality influences market reactions in Seasoned Equity Offerings (SEOs). Using a sample of 146 SEOs from 106 unique firms between 2005 and 2024, we analyze whether foreign investor versus domestic investor participation systematically affects market reactions. Foreign-backed SEOs are initially found to generate less negative abnormal returns than domestic offerings. However, this premium disappears once firm-specific factors and fixed effects are controlled for. Sector and crisis-year analyses reveal that foreign investor participation is positively received by the market in some industries with up to a 24% increase in cumulative abnormal return (CAR), while in times of market downturns, SEOs involving foreign investors experience negative CAR by up to -15.8% Overall, the valuation impact of foreign capital is conditional, highlight the importance of investor nationality in the context of equity issuance strategy. This study contributes to the SEO literature by providing new evidence on how investor nationality interacts with sector complexity and market cycles to influence market reactions and offers new insights for firms raising equity in increasingly internationalized capital markets
Keywords: Seasoned Equity Offerings; Investor identity; Sector heterogeneity; Abnormal returns; Information asymmetry